Mandatory monthly outpatient visits could improve therapeutic inertia in patients with poorly controlled type 2 diabetes - Ying‐Ying Tsai; Ting‐Yu Kuo; Meng‐Hung Lin; Feng‐Chih Shen; Yung‐Hsiang Lin (Journal of Diabetes Investigation, 2024)
ABSTRACT Aims/Introduction Delayed intensification of treatment, or therapeutic inertia, increases the risk of diabetic complications and death. The aim of this study was to determine the effect of mandatory monthly outpatient visits on therapeutic inertia in patients with suboptimal control of type 2 diabetes. Materials and Methods This retrospective cohort study used data from the Chang Gung Research Database and defined two study periods: the baseline period and the intervention period. The intervention period began when the Kaohsiung branch initiated a mandatory monthly outpatient visits program. Type 2 diabetes patients with baseline glycated hemoglobin (HbA1c) >7% and a follow‐up HbA1c measurement were enrolled in each period, and divided into a Kaohsiung branch (intervention) group and the other branches (control) group. Therapy intensification was evaluated by comparing prescriptions after the follow‐up HbA1c measurement with the prescriptions after the baseline HbA1c measurement. Results A total of 5,045 patients at the Kaohsiung branch and 13,400 participants at other branches were enrolled in the baseline period; and 5,573 and 15,603 patients, respectively, were enrolled in the intervention period. The adjusted odds ratio (AOR) for therapy intensification in patients with baseline HbA1c ≥9% was not significantly higher at 1.21 (95% CI, 1.00–1.47) in the intervention period at the Kaohsiung branch, but was significantly higher (AOR, 1.53; 95% CI, 1.02–2.30) in the subgroup with worsened HbA1c. Conclusions Mandatory monthly outpatient visits could improve therapeutic inertia in patients with poorly controlled type 2 diabetes, especially in those with worsened control. The trajectory of HbA1c could significantly influence the assessment of the prevalence of therapeutic inertia.